2011
DOI: 10.1111/j.1365-2591.2011.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the surface of four calcium silicate‐containing endodontic materials and an epoxy resin‐based sealer after a solubility test

Abstract: AH Plus and MTA-A were in accordance with ANSI/ADA's requirements regarding solubility whilst iRoot SP, MTA Fillapex and Sealapex did not fulfil ANSI/ADA's protocols. High levels of Ca(2+) ion release were observed in all materials except AH Plus. SEM/EDX analysis revealed that all samples had morphological changes in both outer and inner surfaces after the solubility test. High levels of calcium and carbon were also observed at the surface of all materials except AH Plus and MTA-A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
173
1
43

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(241 citation statements)
references
References 29 publications
24
173
1
43
Order By: Relevance
“…In the present study, MTA Fillapex high dissolution rate was demonstrated in all tested periods. Similar results have been previously reported (21) showing that this material has a higher dissolution rate than the 3% recommended by ISO specification (ISO 10993-5). This higher dissolution rate may account for a greater sealer particles release during the elution in DMEM, resulting in a higher exposition of MTA Fillapex and a mechanical aggression to the cell culture.…”
Section: Resultssupporting
confidence: 80%
“…In the present study, MTA Fillapex high dissolution rate was demonstrated in all tested periods. Similar results have been previously reported (21) showing that this material has a higher dissolution rate than the 3% recommended by ISO specification (ISO 10993-5). This higher dissolution rate may account for a greater sealer particles release during the elution in DMEM, resulting in a higher exposition of MTA Fillapex and a mechanical aggression to the cell culture.…”
Section: Resultssupporting
confidence: 80%
“…MTA Fillapex and Sankin Apatite III contain polymers susceptible to polymerization shrinkage. Moreover, despite the manufacturer of EndoSequence BC claiming that the product contains no polymers, independent researchers had identified the presence of carbon polymer which had not been previously reported by the manufacturer 36) . EDTA (17%) was used as an irrigant in this study, as it had been demonstrated to decrease the wetting ability of dentinal walls 37) , thereby producing an environment suitable for the adhesion of hydrophobic materials such as AH Plus.…”
Section: Discussionmentioning
confidence: 99%
“…The superior adaptation of AH Plus could be due to its ability to bond to root dentin chemically by reacting with any exposed amino groups in collagen to form covalent bonds between the epoxy resin and collagen 28) . Unlike alkaline bioceramic-based sealers 36) , AH Plus is slightly acidic and might result in selfetching when in contact with dentin, thereby enhancing interfacial bonding and adaptation 37) . Furthermore, the alkaline nature of many bioceramic by-products has been reported to denature dentinal collagen fibers, which then facilitated the penetration of sealers into the dentinal tubules 12) .…”
Section: Discussionmentioning
confidence: 99%
“…The resin components of MTA Fillapex might adversely affect its bonding to dentin and sealing properties (30). Using scanning electron microscopy, Barges et al (31) found that exposing MTA Fillapex specimens to deionized water results in porosities and cracks in the resin matrix. Energy-dispersive spectroscopy confirmed this polymer degradation and a decrease in the carbon element.…”
Section: Discussionmentioning
confidence: 99%